2021
DOI: 10.3390/molecules26144214
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dialkylamino-Functionalized Chalcone, DML6, Inhibits Cervical Cancer Cell Proliferation, In Vitro, via Induction of Oxidative Stress, Intrinsic Apoptosis and Mitotic Catastrophe

Abstract: In this study, we designed, synthesized and evaluated, in vitro, novel chalcone analogs containing dialkylamino pharmacophores in the cervical cancer cell line, OV2008. The compound, DML6 was selective and significantly decreased the proliferation of OV2008 and HeLa cells in sub-micromolar concentrations, compared to prostate, lung, colon, breast or human embryonic kidney cell line (HEK293). DML6, at 5 μM, arrested the OV2008 cells in the G2 phase. Furthermore, DML6, at 5 μM, increased the levels of reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…[ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Furthermore, induction of both intrinsic and extrinsic apoptosis pathways associated with caspases activation, modulation of the Bcl-2 family protein activity, impairment of mitochondrial function with subsequent release of proapoptotic factors such as cytochrome c has also been experimentally proven [ 27 , 28 ]. Some of the above-mentioned effects have also been demonstrated by experiments from our laboratory [ 14 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Furthermore, induction of both intrinsic and extrinsic apoptosis pathways associated with caspases activation, modulation of the Bcl-2 family protein activity, impairment of mitochondrial function with subsequent release of proapoptotic factors such as cytochrome c has also been experimentally proven [ 27 , 28 ]. Some of the above-mentioned effects have also been demonstrated by experiments from our laboratory [ 14 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones have been demonstrated to inhibit tumor progression and development in cancers [12][13][14][15][16][17][18], including glioma [15,18]. The synthetic Chalcone 9X is an aromatic ketone, which has been proved to own antitumor activities in lung cancer cells and hepatic cancer cells through activating Caspase-3 and Caspase-8 signaling pathway [19].…”
Section: Discussionmentioning
confidence: 99%
“…Natural and chemical synthetic chalcones have been revealed to play critical roles in some biological functions, such as inflammation [7][8][9] and antibacterial effects [10,11]. Furthermore, more studies demonstrated that chalcones could inhibit tumor progression in various cancers [12][13][14][15][16][17][18][19], including glioma [15,18]. For example, Mendanha et al found that Chalcone 1 could induce cell apoptosis of glioblastoma (GBM), which was triggered by the cell cycle arrest in the G2/M checkpoint, and might be a potential to provide a new treatment alternative for GBM 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones also present a wide activity against different diseases, which became a good fragment for the diversity of biological activities and an important synthetic intermediate. [15][16][17] Among the biological activities, chalcone derivatives have been reported as antiproliferative agents due to their ability to induce apoptosis, [20][21][22][23] and mitotic catastrophe by increasing proapoptotic proteins, as well as increasing the levels of reactive oxygen species that collapse the mitochondrial membrane potential, [20] repress cell proliferation and migration capacities through activating caspases (3,7,8, or 9) signaling pathway, [21] and affect cell cycle changes, [22,23] inhibiting the growth of different cancer cell such as cervical cancer, [20] breast cancer, [22] hepatic cancer and lung cancer. [21] Furthermore, chalcones have been also evaluated as potential antifungal, [24] antibacterial, [25] and antiviral [26] agents.…”
mentioning
confidence: 99%